HIV-1 gp120 Promotes Lysosomal Exocytosis in Human Schwann Cells - Datta, Gaurav; Miller, Nicole M.; Afghah, Zahra; Geiger, Jonathan D.; Chen, Xuesong (Frontiers in Cellular Neuroscience, 2019)
HIV-1 associated neuropathy is the most common neurological complication of HIV, with debilitating pain affecting the quality of life. HIV-1 gp120 plays an important role in the pathogenesis of HIV neuropathy via direct neurotoxic effects or indirect pro-inflammatory responses. Studies have shown that gp120-induced release of mediators from Schwann cell induce CCR5-dependent DRG neurotoxicity; However, CCR5 antagonists failed to improve pain in HIV infected individual. Thus, there is an urgent need for better understanding its pathogenesis and developing effective therapeutic strategies. Because lysosomal exocytosis in Schwann cells is an indispensable process for regulating myelination and demyelination, we determined the extent to which gp120 affected lysosomal exocytosis in human Schwann cells. We demonstrated that gp120 promoted the movement of lysosomes towards plasma membrane, induced lysosomal exocytosis, and increased the release of ATP into the extracellular media. Mechanistically, we demonstrated lysosome de-acidification, and activation of P2X4 and VNUT to underlie gp120-induced lysosome exocytosis. Functionally, we demonstrated that gp120-induced lysosome exocytosis and release of ATP from Schwann cell lead to increase in intracellular calcium and generation of cytosolic reactive oxygen species in DRG neurons. Our results suggest that gp120-induced lysosome exocytosis and the release of ATP from Schwann cells affect DRG neurons function and contribute to pathogenesis of HIV-1 associated neuropathy.